Permeability and frictional strength of cation‐exchanged montmorillonite. Issue 6 (14th June 2013) - Behnsen, J.; Faulkner, D. R.
Abstract : [1] Smectites, such as montmorillonite, are abundant throughout the upper crust and are commonly found in fault gouge. They are known for their weak frictional strength and low permeability. Smectites are swellable clays in which the interlayer cation can easily be exchanged. In this study, we measure permeability and frictional strength of montmorillonite exchanged with Na +, K +, Ca 2+, and Mg 2+ using a triaxial shear apparatus. We find that the interlayer cation influences both permeability and the friction coefficient. K‐montmorillonite is significantly stronger ( μ =0.26) than Na‐montmorillonite ( μ =0.15) and Ca‐ or Mg‐montmorillonite ( μ =0.11). Permeability for all four clays is between 10 −21 and 10 −23 m 2 in the pressure range between 10 MPa and 100 MPa, with K‐montmorillonite the most permeable clay gouge. Mg‐, Ca‐, and Na‐montmorillonite show relative similar permeabilities of which Na‐montmorillonite is least permeable. We relate the higher frictional strength and permeability of K‐montmorillonite to reduce interlayer water content caused by differences in cation hydration and adsorption. The results show that the rapid cation exchange process in montmorillonite can influence macroscale parameters, such as permeability and strength, which can contribute to changes in local pressure conditions and frictional strength of shallow fault zones. Key Points: Studied frictional strength and permeability of cation‐exchanged smectites K‐montmorillonite is frictionally stronger than Na‐, Ca‐, Mg‐montmorillonite K‐montmorillonite is more permeable than Na‐, Ca‐, Mg‐montmorillonite